Tensile mechanical properties of human forearm tendons. (September 2015) - Weber, J. F.; Agur, A. M. R.; Fattah, A. Y.; Gordon, K. D.; Oliver, M. L.
Previous studies of the mechanical properties of tendons in the upper limb have used embalmed specimens or sub-optimal methods of measurement. The aim of this study was to determine the biomechanical properties of all tendons from five fresh frozen cadaveric forearms using updated methodology. The cross-sectional area of tendons was accurately measured using a laser reflectance system. Tensile testing was done in a precision servo-hydraulic device with cryo-clamp fixation. We determined that the cross-sectional area of some tendons is variable and directly influences the calculated material properties; visual estimation of this is unreliable. Data trends illustrate that digital extensor tendons possess the greatest tensile strength and a higher Young's modulus than other tendon types.